A REPLICABLE MODEL FOR VALUING LOCAL FOOD SYSTEMS. (2nd September 2015) - MILLER, STEVEN R.; MANN, JOHN; BARRY, JUDITH; KALCHIK, TOM; PIROG, RICH; HAMM, MICHAEL W.
Abstract: We use the underlying data of the IMPLAN Pro 3.0 regional economic simulation model to estimate the current economic contribution of Michigan's local food system and explore the chain of transactions giving rise to consumption of locally sourced goods from producer to processor to consumption. The proposed methodology includes both unprocessed and processed foods in the estimation of the local food system's economic value. The model also provides a replicable and consistent approach to estimating the value of local food systems within regional and state economies.